High levels of plasma interleukin-17A are associated with severe neurological sequelae in Langerhans cell histiocytosis. (February 2020) - Ismail, Mohamad Bachar; Åkefeldt, Selma Olsson; Lourda, Magda; Gavhed, Désirée; Aricò, Maurizio; Henter, Jan-Inge; Delprat, Christine; Valentin, Hélène
Highlights: High levels of plasma IL-17A were found in LCH patients. IL-17A was associated with LCH patients, especially those having sequelae. High levels of IL-17A were found in patients with neurodegenerative LCH. IL-17A may be associated with the development of neurodegenerative LCH. Abstract: Objective: Langerhans cell histiocytosis (LCH) is a granulomatous inflammatory myeloid neoplasia associated with a cytokine storm in both serum and lesions. Increased levels of plasma interleukin-17A (IL-17A) in LCH patients have been reported, but this finding was not confirmed in all studies. Neurodegeneration is a devastating complication of LCH (ND-LCH). We aimed to revisit the issue of plasma IL-17A levels in LCH, by using a larger number of patients, and also to investigate the relationship between IL-17A and LCH sequelae, especially ND-LCH. Methods: Plasma samples from 68 LCH patients and 127 controls were analyzed for IL-17A levels by two ELISAs with different anti-IL-17A capture antibodies: either polyclonal or neutralizing monoclonal antibodies in 17polyAb-ELISA or 17mAb-ELISA, respectively. Results: Both ELISAs had a similar capacity to specifically detect recombinant or native human IL-17A, as well as plasma IL-17A from LCH patients. We confirmed the finding of higher levels of plasma IL-17A in LCH patients compared to controls (p < 0.0001). The association of IL-17A with LCH was independent of the ELISA used, and of gender, age, disease class activity, and pattern of tissue-organ involvement (single-system versus multi-system). ROC analyses (p < 0.0001) allow to discriminate LCH patients from the control group, supporting the notion that IL-17A may be a potential biomarker for LCH. More interestingly, high IL-17A levels were significantly associated with LCH patients having sequelae, with the highest plasma levels in patients with ND-LCH (p < 0.0001). Conclusion: The association between high levels of IL-17A and LCH was confirmed. IL-17A may be associated with ND-LCH development. This might have therapeutic implications, offering a novel target for precision therapy of ND-LCH.